Scrotal/testicular status after repair of recent severe incarcerated inguinal hernia in male infants younger than 12 months old: Laparoscopic percutaneous extraperitoneal closure versus conventional open repair. Issue 4 (19th December 2018) - Miyano, Go; Nakamura, Hiroki; Shibuya, Soichi; Ochi, Takanori; Yazaki, Yuta; Murakami, Hiroshi; Seo, Shogo; Okawada, Manabu; Doi, Takashi; Koga, Hiroyuki; Lane, Geoffrey J; Yamataka, Atsuyuki
Abstract: Introduction: We prospectively reviewed 41 male infants younger than 12 months old who had presented with severe incarcerated inguinal hernia between 2014 and 2016 and had been treated by laparoscopic percutaneous extraperitoneal closure (LPEC) or conventional open repair (CO). Methods: Operative times and intraoperative findings were evaluated. Scrotal/testicular status were assessed preoperatively, 1 week, and 4 weeks after surgery. Results: There were 21 boys treated by LPEC and 20 by CO. Mean ages and mean weights at surgery were similar between the groups. The mean operative time was 19.7 min for LPEC and 45.8 min for CO ( P < 0.05). The peritoneum was edematous in 13 LPEC cases (61.9%). Wound infection was observed in one CO case and in one LPEC case at the umbilicus. Postoperative scrotal/testicular swelling was observed in four cases at 1 week and two cases at 4 weeks among the CO cases and in one case at 1 week and no cases at 4 weeks among the LPEC cases ( P  = not significant). Postoperative testicular elevation was observed on the operated side in two CO cases and in no LPEC cases at 1 and 4 weeks ( P  = not significant). There has been no recurrence or testicular atrophy in either group. Conclusion: Performing LPEC took significantly less time than performing CO. Although no statistically significant differences in scrotal/testicular status were identified, a larger study is warranted to prove that LPEC is associated with less surgical stress than CO.